2018
DOI: 10.1115/1.4041838
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Performance Study of Double Basin Single Slope Solar Still With and Without Using Nanoparticles

Abstract: In major region of the world, ample amount of fresh water is required for the drinking purpose as well as for the agricultural and industrial growth. Hence, it is necessary to investigate the alternate clean water extraction technologies to get the potable water from the saline water available at local area or inside the earth. One of the methods used to get the fresh water from the brackish water is solar distillation and the means used is called as a solar still. In the present work, single slope double basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In another studied Modi et al, [13] performed the experimentation on single slope double basin solar still with Al2O3 nanoparticles. During experimentation the mass of Al2O3 nanoparticles was varied i.e.…”
Section: Nanoparticlementioning
confidence: 99%
“…In another studied Modi et al, [13] performed the experimentation on single slope double basin solar still with Al2O3 nanoparticles. During experimentation the mass of Al2O3 nanoparticles was varied i.e.…”
Section: Nanoparticlementioning
confidence: 99%
“…Modi et al evaluated the influence of Al 2 O 3 nanoparticles at different configurations on distillate production. It was found that the 0.01% concentration of Al 2 O 3 nanoparticles had improved the distillate yield by about 18% which was high compared to other cases 9 . Panchal et al studied the distillate production of solar still using manganese dioxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the 0.01% concentration of Al 2 O 3 nanoparticles had improved the distillate yield by about 18% which was high compared to other cases. 9 Panchal et al studied the distillate production of solar still using manganese dioxide nanoparticles. It was noted that the solar still with nanoparticles improved the distillate output by 19.5% compared to CSS.…”
mentioning
confidence: 99%
“…Another experiment used Al 2 O 3 nanoparticle of varying concentration in the basin of solar still. They observed that by using nanoparticle, the distilled output is increased by 2.6%,7.2%, 12.3%, and 17.6% for weight concentrations of 0.2%, 0.10%, 0.05%, and 0.01%, respectively, in comparison with solar still without nanoparticles 24 . Single‐basin dual‐slope solar still along with Al 2 O 3 with varying depth of 0.010, 0.020, and 0.030 m was used for experiment.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that by using nanoparticle, the distilled output is increased by 2.6%,7.2%, 12.3%, and 17.6% for weight concentrations of 0.2%, 0.10%, 0.05%, and 0.01%, respectively, in comparison with solar still without nanoparticles. 24 Single-basin dual-slope solar still along with Al 2 O 3 with varying depth of 0.010, 0.020, and 0.030 m was used for experiment. Enhanced productivity of 1.252, 1.220, and 1.120 L was observed in comparison to conventional solar still, which has distillate output 0.989, 0.950, and 0.938 L with a depth of 0.010, 0.020, and 0.030 m, respectively.…”
Section: Introductionmentioning
confidence: 99%